Incidence of peripheral arterial disease in eastern part of Uttar Pradesh, India in a tertiary hospital and its management - Singh, Sanjay; Singh, Mayurika; Kola, Anish (International Surgery Journal, 2018)
Background: Peripheral artery diseases, group of some pathological conditions affecting limbs are chronic and gradually progressing causing limitation in blood flow. to assess the incidence, related factors and treatment comparison of peripheral arterial diseases in eastern part of Uttar Pradesh. Methods: All the patients come to OPD with suspected peripheral arterial disease are evaluated with proper history taking, investigation and diagnosed the specific pathology and treated accordingly. From these 40 patients conclusions have been made. Results: Majority of the patients were suffered from thromboangitis obliterans (42.55%). Arteriosclerosis obliterans constitute only 12.55% of peripheral arterial disorders.25%were congregation of miscellaneous arterial disorders viz. Rheumatoid arthritis (3 cases), infective gangrene and non-healing ulcers (5 cases) and 2 cases of arteriovenous fistula. Conclusions: Most common peripheral arterial disease is thromboangitis obliterans. Males are commonly affected by peripheral arterial diseases. But incidence of Buerger’s disease increase in females because of increasing habits of smoking and tobacco addiction in any form. Most of patients of T.A.O were villagers while A.S.O, diabetic arteriopathy, vasospastic disease and rheumatoid arthritis commonly affected urban population. Sympathectomies yields good results in early stages of thromboangitis obliterans and vasospastic disease.